Seimbangkan Game Online dengan Game Offline di Era Revolusi Industri 4.0 - Husniah Ramadhani Pulungan (Studi Multidisipliner: Jurnal Kajian Keislaman, 2019)
This article aims to strike a balance between online games that have some negative impacts and offline games (which are paired with the term sports or games) in the era of the industrial revolution 4.0. The method used is descriptive qualitative with a case study because the source of the data is from the uti-utian of the Angkola tribe which originates from a written document titled "Adat budaya Batak Angkola menelusuri perjalanan masa". The results revealed three categories of uti-utian namely: children's games, dexterity, and the device to block. Cultural themes resulting from these three categories include: being able to practice fitness, agility, positive social interactions (cooperation, honesty, sportsmanship, solidarity, solidarity, tolerance, patience, agility, being smart in looking for opportunities, clever in finding solutions), learning to appreciate victory, tolerant defeat, clear-minded, and the most important thing is to be happy in life. Thus, this study can still be developed in further research by deepening the comparison of the types of online games that continue to develop which are equivalent to the types of offline games based on deeper arguments.